MCDM Approach to Assess Innovation and Entrepreneurship Education in Higher Vocational Colleges under IndetermSoft Set - Mingfang Liu; Chuang Li (Neutrosophic Sets and Systems, 2025)
Innovation and entrepreneurship education has become an essential component of higher vocational colleges, aiming to cultivate students' creativity, problem-solving abilities, and business acumen. As the global economy increasingly prioritizes innovation-driven development, vocational institutions must ensure that their educational programs align with industry demands and entrepreneurial ecosystems. However, assessing the quality of innovation and entrepreneurship education remains a complex challenge due to the interdisciplinary nature of the field, the diverse skill sets required, and the rapidly evolving business environment. We use the concept of multi-criteria decision-making (MCDM) to deal with different criteria. Two MCDM methods are used in this study such as Entropy method to compute the criteria weights and the EDAS method to rank the alternatives. we use the IndetermSoft set to deal with indeterminacy in criteria values. We propose an application to show the validation of the proposed approach. DOI: 10.5281/zenodo.15036578